Kinetics and mechanism of the ligand substitution reaction of di-μ- hydroxobis(bipyridyl)dipalladium(II) ion with N,N’-diethylthiourea in aqueous solution - Mallick Subhasis; Nandi Debabrata; Mandal Arup; Mondal Subala; Bera Biplab Kumar; Karmakar Parnajyoti; Ghosh Alak Kumar (International Journal of Research in Chemistry and Environment (IJRCE), 2011)
The interaction of the title complex with N,N'-diethylthiourea (DETU) has been studied spectrophotometrically in aqueous medium as a function of [substrate complex], [ligand], and temperature at a particular pH (7.4), where the substrate complex exists predominantly as the dimeric dihydroxobridged species at constant ionic strength. The reaction has been monitored at 300 nm, the λmax of the substituted complex, where the spectral difference between the reactant and the product is maximum. The reactions have been studied under pseudo-first order conditions. The reaction proceeds in a two-step-consecutive manner (A → B → C) where the first step is the ligand dependent and second step is the ligand independent and is assigned to formation of chelate ring. The reaction rate increases with increase in [ligand] before reaching a limiting value which is probably due to the completion of the outer-sphere association complex formation. At this stage the interchange of the ligands from the outer-sphere to the inner- sphere occurs. The activation parameters calculated from Eyring plots are: DH1¹ = 44.0 ± 1.5 kJ mol-1, DS1¹ = -147 ± 5 JK-1mol-1, DH2¹ =17.8 ± 0.8 kJ mol-1, DS2¹ = -278 ± 2 JK-1 mol-1. Based on the kinetic and activation parameters an associative interchange mechanism is proposed for the interaction processes. The product of the reaction has been characterized, as conductance measurement and IR spectroscopic analysis. Comparison of the kinetic and thermodynamic parameters of the interaction of N, N'-diethylthiourea and thiourea with the reactant complex, it is clear that steric effect plays an important role in determining the reactivity of the incoming nucleophile for an associative mode of activation.